AN EXAMINATION OF THE SUZUKI VIOLIN SCHOOL BOOK II IN TERMS OF THE RIGHT-HAND AND LEFT-HAND TECHNIQUES - TANINMIŞ, Gamze Elif; KAHRAMAN, Gizem (Atlas Journal, 2022)
This study aims to reveal right-hand and left-hand techniques included in Suzuki Violin School Book II. It is a descriptive study conducted by using content analysis model among qualitative research methods. The study tabulates right-hand and left-hand techniques addressed in 12 musical pieces to be taught to students in Suzuki Violin School Book II. The book consists of musical pieces for the development and refinement of the techniques learned in the first volume of the work. Book II contains practices on bow techniques, bow uses (partitions) and finger alignments different from those in the first book, and application of musical dynamics to all note values learned with a correct bow technique. In this book, each section shows more than one right-hand and left-hand techniques and they are arranged in an order of increasing difficulty and complexity starting from the simples and easiest examples. It is recommended to continue with the sequels after finishing Suzuki Violin School Book II. Also, some studies were carried out to assist students and instructors working with the Suzuki method. It is recommended to replicate those studies for other Suzuki Violin School books.